Emergence of hystricognathous rodents: Palaeogene fossil record, phylogeny, dental evolution and historical biogeography - (:unkn) unknown (My University, 2019)
Although phylogenetic trees imply Asia as the ancestral homeland of the Hystricognathi clade (Rodentia: Ctenohystrica), curiously the oldest known fossil occurrences of hystricognathous rodents are not from Asia, but from Africa and South America, where they appear suddenly in the fossil record of both landmasses by the Late Middle Eocene. Here we performed cladistic and Bayesian (standard and tip-dating analyses) assessments of the dental evidence documenting early ctenohystricans, including several Asian 'ctenodactyloids', virtually all Palaeogene Asian and African hystricognaths known thus far and two representatives of the earliest known South American hystricognaths. Our results provide a phylogenetic context of early hystricognaths (with implications on systematics) and suggest that some Eocene Asian 'ctenodactyloids' could be considered as stem hystricognaths and pre-hystricognaths, although they were not recognized as such originally. However, this view does not fill the gap of the Eocene Asian hystricognath record, as the proposed results imply many ghost lineages extending back to the Middle Eocene for several Asian and African taxa. They also imply a complex early historical biogeography of the group, involving multiple dispersal events from Asia to Africa (and possibly from Africa back to Asia) and then to South America sometime during the Middle Eocene. Based on these phylogenetic considerations, we discuss the emergence of hystricognathous rodents from a morpho-anatomical perspective by analysing the differentiation of their masticatory apparatus and chewing movements; notably, evolution of their dental patterns.
Keywords: African Research